Ectopic GRHL2 Expression Due to Non-coding Mutations Promotes Cell State Transition and Causes Posterior Polymorphous Corneal Dystrophy 4 - Liskova, Petra; Dudakova, Lubica; Evans, Cerys J; Rojas Lopez, Karla E; Pontikos, Nikolas; Athanasiou, Dimitra; Jama, Hodan; Sach, Josef; Skalicka, Pavlina; Stranecky, Viktor; Kmoch, Stanislav; Thaung, Caroline; et al. (American journal of human genetics, 2018)
In a large family of Czech origin, we mapped a locus for an autosomal-dominant corneal endothelial dystrophy, posterior polymorphous corneal dystrophy 4 (PPCD4), to 8q22.3-q24.12. Whole-genome sequencing identified a unique variant (c.20+544G>T) in this locus, within an intronic regulatory region of GRHL2. Targeted sequencing identified the same variant in three additional previously unsolved PPCD-affected families, including a de novo occurrence that suggests this is a recurrent mutation. Two further unique variants were identified in intron 1 of GRHL2 (c.20+257delT and c.20+133delA) in unrelated PPCD-affected families. GRHL2 is a transcription factor that suppresses epithelial-to-mesenchymal transition (EMT) and is a direct transcriptional repressor of ZEB1. ZEB1 mutations leading to haploinsufficiency cause PPCD3. We previously identified promoter mutations in OVOL2, a gene not normally expressed in the corneal endothelium, as the cause of PPCD1. OVOL2 drives mesenchymal-to-epithelial transition (MET) by directly inhibiting EMT-inducing transcription factors, such as ZEB1. Here, we demonstrate that the GRHL2 regulatory variants identified in PPCD4-affected individuals induce increased transcriptional activity in vitro. Furthermore, although GRHL2 is not expressed in corneal endothelial cells in control tissue, we detected GRHL2 in the corneal "endothelium" in PPCD4 tissue. These cells were also positive for epithelial markers E-Cadherin and Cytokeratin 7, indicating they have transitioned to an epithelial-like cell type. We suggest that mutations inducing MET within the corneal endothelium are a convergent pathogenic mechanism leading to dysfunction of the endothelial barrier and disease.
Keywords: sekvenování celého genomu; Genetic Loci; sekvence nukleotidů; Male; Pedigree; mutace; genetické lokusy; rodina; rodokmen; dědičné dystrofie rohovky; Family; PPCD; corneal dystrophy; HEK293 buňky; GRHL2; intergenová DNA; corneal edema; Transcription, Genetic; corneal endothelium; mesenchymal-to-epithelial transition; HEK293 Cells; promotorové oblasti (genetika); mužské pohlaví; DNA vazebné proteiny; Endothelium, Corneal; Models, Genetic; epithelial-to-mesenchymal transition; non-coding mutation; regulatory region; ectopic expression; Introns; genetická transkripce; rohovkový endotel; introny; lidé; Transcription Factors; ženské pohlaví; transkripční faktory; Humans; Promoter Regions, Genetic; Corneal Dystrophies, Hereditary; modely genetické; DNA, Intergenic; Base Sequence; Mutation; Female; DNA-Binding Proteins; Whole Genome Sequencing